Possibilities of using liquefied oil gas in transport - Kuprys, Algirdas; Kugelevičius, Jonas (Transport, 2009)
The trends of the input of an alternative type of fuel in the transport system of the European Union are analysed. Taking into account the measures of promoting liquefied petroleum gas (LPG) consumption in road transport, a bundle of specific variables was analysed to understand the consumers for making decision to use LPG in cars. It is revealed that the obtained models enable to evaluate the behaviour of consumers and conditioning transition to using an alternative type of fuel in transport industry. The proposed models were assessed conducting statistic and sensitivity analysis. The payoff of the additional equipment of the car was analysed considering the driven distance with an alternative type of fuel. The pay‐off analysis of supplementary equipment depending on the ratio of standard and alternative fuel prices is presented.First published online: 27 Oct 2010